2012
DOI: 10.1590/s1413-23112012000300001
|View full text |Cite
|
Sign up to set email alerts
|

Alinhamento estratégico nas cadeias de suprimento da indústria automobilística brasileira

Abstract: O objetivo do estudo foi analisar o alinhamento nas estratégias de suprimento adotadas pelos elos nas cadeias de suprimentos da indústria automobilística no Brasil. O conceito de alinhamento seguido foi aquele proposto por Vachon et al. (2009), de que o alinhamento se relaciona com a intensidade dos gaps entre os requisitos de um cliente e a ênfase dada por um fornecedor de primeira camada nestes mesmos requisitos ao lidar com os fornecedores de segunda camada. A unidade de análise são empresas industriais loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Na cadeia de suprimentos automotiva, em particular, foi observado que os vínculos entre os fornecedores são enfraquecidos à medida que se afastam da empresa focal, ou seja, há menos colaboração nas relações entre fornecedores de primeira e segunda camada, do que entre a montadora e o fornecedor de primeiro nível (Martins, Souza, & Pereira, 2012 (Jabbour & Souza, 2015).…”
Section: Discussão De Resultadosunclassified
“…Na cadeia de suprimentos automotiva, em particular, foi observado que os vínculos entre os fornecedores são enfraquecidos à medida que se afastam da empresa focal, ou seja, há menos colaboração nas relações entre fornecedores de primeira e segunda camada, do que entre a montadora e o fornecedor de primeiro nível (Martins, Souza, & Pereira, 2012 (Jabbour & Souza, 2015).…”
Section: Discussão De Resultadosunclassified
“…In this sector, new relationship standards between auto manufacturers and suppliers have led the auto parties supply structures into a ranking process (Di Serio et al , 2007; Vanalle and Salles, 2011) by reducing the number of auto manufacturers’ suppliers (Soares, 2011), which started to provide subsets in modules or systems. Consequently, these suppliers have settled near the auto manufacturers, thereof the importance of their location (Vanalle and Salles, 2011; Martins et al , 2012a). According to Soares (2011), auto manufacturers have started to focus on activities that provide higher value-added and competitive advantage by restructuring and strengthening their supplier base and selecting the ones to build a strict relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a relevant aspect because it relates to the importance of building long-term relationships with suppliers, both for material flow and information, which positively affects the competitive performance of organizations through the exchange of complementary competences (Prajogo & Olhager, 2012). In the Brazilian automobile industry, the links between automakers and first tier suppliers are being strengthened, with the objective of obtaining greater coordination in the execution of activities and better access to external resources, for the generation of innovation, increase of productivity and reinforce the competitive capacity (Martins, Souza Filho & Pereira, 2012). Rezende, Lima and Versiani (2012) have shown that the existence of knowledge transfer between buyers (automakers) and suppliers, whether technological, market and logistics, of process or relational, depends on the type of the analyzed knowledge.…”
Section: The Phase Of Management and Adaptation Of Dynamic Capabilitiesmentioning
confidence: 99%
“…Rezende, Lima and Versiani (2012) have shown that the existence of knowledge transfer between buyers (automakers) and suppliers, whether technological, market and logistics, of process or relational, depends on the type of the analyzed knowledge. So, the dependence of a supplier on a specific automaker reinforces the strategic alignment in this supply chain (Martins, Souza Filho, & Pereira, 2012). According to Lemos et al (2000), it is necessary to come closer to suppliers for the development of products with a higher technological level in Brazil, the qualification of workers, for institutional incentives and funding.…”
Section: The Phase Of Management and Adaptation Of Dynamic Capabilitiesmentioning
confidence: 99%